Pl. answer this question

Asked by  | 16th Feb, 2010, 05:36: PM

Expert Answer:

a(x2+1) -  x(a2+1) = 0 

ax2 -  (a2 + 1)x + a   = 0

x = {(a2 + 1) ± [(a2 + 1)2-4a2]}/2a

= {(a2 + 1) ± [(a4 + 2a2+ 1 - 4a2]}/2a

= {(a2 + 1) ±[(a4 - 2a2+ 1]}/2a

= {(a2 + 1) ±[(a2 - 1]}/2a

= a and 1/a

Writing  the quadratic  equation, in standard roots form, i.e. x2- (α+β)x + αβ = 0 

x2- (a + 1/a)x + 1 = 0

ax2 - (a2+1)x + a = 0

which is exactly identical to the given quadratic equation.

Regards,

Team,

TopperLearning.

Answered by  | 16th Feb, 2010, 06:37: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.